In vitro Candida albicans biofilm formation on different titanium surface topographies - Mathieu Mouhat; Robert Moorehead; Craig Murdoch (Medical Journals Sweden, 2020)
Objectives To investigate if differences in titanium implant surface topography influence Candida albicans biofilm formation. Materials and Methods Titanium discs were prepared and characterized using a profilometer: Group A (Ra 0.15 µm, smooth), Group B (Ra 0.64 µm, minimally rough) and Group C (Ra 1.3 µm, moderately rough). Contact angle and surface free energy (SFE) were determined for each group. Non-preconditioned titanium discs were incubated with C. albicans for 24 h. In additional experiments, the titanium discs were initially coated with human saliva, bovine serum albumin or phosphate-buffered saline for 2 h before incubation with C. albicans for 24 h. The amount of fungal biofilm formation was quantified using a colorimetric assay. Results C. albicans biofilm formation was significantly lower (p < 0.05) on the minimally rough titanium surface compared to smooth and moderately rough surfaces. The titanium surface displaying the lowest SFE (Group B) was associated with significantly lower (p < 0.05) C. albicans biofilm formation than the other two groups. Salivary coating resulted in greater adherence of C. albicans with increased surface roughness. Conclusions The minimally rough titanium discs displayed lowest SFE compared to smooth and moderately rough surfaces and showed the least C. albicans biofilm formation. This study demonstrated that C. albicans biofilm formation increased in a SFE-dependent manner. These findings suggest that SFE might be a more explanatory factor for C. albicans biofilm formation on titanium surfaces than roughness. The presence of a pellicle coating may negate the impact of SFE on C. albicans biofilm formation on titanium surfaces.